Evidence-based clinical practice guidelines on the management of pain in older people – a summary report. Issue 1 (February 2022) - Schofield, Patricia; Dunham, Margaret; Martin, Denis; Bellamy, Gary; Francis, Sally-Anne; Sookhoo, Dave; Bonacaro, Antonio; Hamid, Eshtar; Chandler, Rebecca; Abdulla, Aza; Cumberbatch, Mike; Knaggs, Roger
Objective: The objective of this study is to develop an update of the evidence-based guidelines for the management of pain in older people. Design: Review of evidence since 2010 using a systematic and consensus approach is performed. Results: Recognition of the type of pain and routine assessment of pain should inform the use of specific environmental, behavioural and pharmacological interventions. Individualised care plans and analgesic protocols for specific clinical situations, patients and health care settings can be developed from these guidelines. Conclusion: Management of pain must be considered as an important component of the health care provided to all people, regardless of their chronological age or severity of illness. By clearly outlining areas where evidence is not available, these guidelines may also stimulate further research. To use the recommended therapeutic approaches, clinicians must be familiar with adverse effects of treatment and the potential for drug interactions.